Pelatihan Metode Repetitive Learning Dalam Mengembangkan Kecerdasan Kognitif Anak Usia Dini - Hestiyanah Hestiyanah; Rihatul Jannah; Minhatul Ma’arif; Badri Munawar; Reni Suwenti (Pusat Riset dan Inovasi Nasional, 2023)
Education is a very important level for every individual, especially at the golden age, early childhood education is the first education for children before they enter a higher level of education such as elementary school. To prepare things and various intelligences possessed by children, especially cognitive intelligence, effective and interesting learning methods are held, one method that is suitable for early childhood learning is the repetitive or repetition method. This method is applied to early childhood in Citeureup Village, precisely in the Sumurjaya Village, for early childhood to be provisioned when they enter elementary school education. The purpose of applying this repetitive method is so that pre-school children in the Sumur Jaya village are more mature and ready to go to elementary school. The research method used in this research is qualitative. The result after this research was carried out, there was a significant change in the introduction of learning for early childhood